Diseño de un sistema de bombeo alimentado mediante paneles solares fotovoltaicos para riego en un cultivo de ñame en el municipio del Carmen de Bolívar, Colombia. (2022)
This project presents the design of a water pumping system (drip irrigation) which was electrically powered by photovoltaic solar panels for a yam crop in Carmen de Bolívar, Colombia. The methodology used was divided into 3 phases: the first phase is the agronomic, water and design conditions study of the pumping system that will be powered by solar panels. The foregoing began with the analysis of the environmental conditions of the extension of land, solar radiation, spacing, water reserves and space for the implementation of the system, among other factors. Second, the elements of the pumping system and energy supply system that meet the demand required by the implementation of the irrigation system were determined through a technical analysis. Finally, the feasibility and cost study of the project was carried out considering the design considerations and the technical considerations of the same to generate a cost-effective proposal for the system. With the results, the assisted drip irrigation system was dimensioned, which had a pump connected to solar energy for the specified land (half a hectare). The calculations showed that the pump needed for this system is 0.75kW or alternatively 1HP of power.